The role of economic diversification policy in addressing structural imbalances in Algeria - Samia, Zenati; Hanane, Chaoui (The International tax journal, 2026)
This study aims to analyze the role of economic diversification policy in addressing the structural imbalances inherent in the Algerian economy, particularly in light of the excessive reliance on the hydrocarbon sector and the resulting structural fragility and economic fluctuations. The study employs a descriptive-analytical approach by reviewing economic literature and analyzing a set of indicators related to the economic structure, such as the composition of Gross Domestic Product (GDP), inflation, and unemployment rates. The findings indicate that despite the significance of the efforts made toward economic diversification, they have not yet achieved the desired impact in correcting structural imbalances. The hydrocarbon sector continues to dominate economic activity, contrasted by the weak contribution of other productive sectors such as agriculture and tourism. The study concludes that achieving effective and sustainable economic diversification requires the adoption of profound structural reforms based on the development of non-oil sectors.